(untitled) (World Science, 2022)
Depending on the nature and characteristics of the heavy metals that accumulate on the surface of the soil, separated from vehicle waste around the highway, they migrate downwards in the soil profile. The course of this process and the properties of heavy metals have been studied by many researchers. The migration of heavy metals in the soil profile later leads to the contamination of plants, especially agricultural crops, with toxic substances. It enters the food chain around the highway, especially with the more intensive accumulation of lead. It is considered dangerous for animals when the amount of lead in dry fodder plants is 100 mg/kg. Its amount migrates deep into the soil profile for several years and remains in the soil for many years without losing its effect. Until recent years, tetraethyl lead was added to all fuels to increase its combustibility and increase the deformation pressure, which caused the release of 200 400 mg of lead into the atmosphere during the combustion of one liter of gasoline. The study found that the migration of heavy metals in the soil profile depends on its granulometric composition, density, thickness of many organic compounds and pH